'Anti-liberal Europe', an opposing narrative to normative power Europe in the Eastern neighbourhood? The case of Georgia. Issue 1 (1st January 2023) - Andguladze, Ana
ABSTRACT: In recent years Georgia saw the rise of anti-liberal, far-right powers, comprised of political parties, societal groups, and media outlets, that found solid ground in exploiting the conflict over values in a predominantly conservative and religious society. While the literature focuses on how different 'non-democratic regional powers' are countering against efforts of Western democracy promotion, including by empowering anti-liberal actors in neighbouring countries, less attention has been paid to the importance of transnational diffusion of ideas from Europe's promoters of 'illiberal democracies' beyond the European Union. This article shows how Georgia's anti-liberal domestic actors have found the 'anti-liberal Europe' as a powerful narrative to pit against 'normative power Europe.' Drawing on frame analysis and analysing how two online outlets have reported about Europe/the European Union from January 2018 to August 2020, this article sheds light on how ultranationalist online media outlets in Georgia are diffusing anti-liberal narratives about Europe, aimed at building a counter-model, an anti-liberal vision pitted against normative power Europe.